Federal Regulation of Substances Generally Recognized As Safe (GRAS) and the Use of Carbon Monoxide in Packaging for Meat and Fish. (U.S. Congressional Research., 2008)
Provides overview of FDA regulation of food additives and Generally Recognized As Safe (GRAS) substances, which are exempt from the premarket approval process for food additives. Discusses FDA 1997 proposed rule to create notification procedure for GRAS substances, and presents statistics on FDA GRAS notices. Addresses roles of USDA and FDA regarding review of substances used in the production of meat and poultry products; examines GRAS notices concerning intended uses of carbon monoxide; and outlines legislative proposals in the 110th Congress.